Sinergi Coexistence Education Based on Tengka and Basudara Values for Mitigating Madura-Papua Conflict Vulnerability: A Qualitative Case Study in Manokwari - Indriyani, Dian; Maimun, Maimun; Hamdani, Hamdani (Jurnal Pendidikan Islam, 2026)
Purpose – This study aims to explain the reality of Madura-Papua conflict vulnerability in Manokwari and the process of internalizing the values of tengka and Basudara, by highlighting the integration of two cultural value systems from migrant communities and Indigenous residents as a conflict mitigation mechanism in a multiethnic social space. Design/methods/approach – This study used a qualitative approach with a single case study design. Data were collected through semi-structured interviews, field observation, and documentation involving 12 purposively selected informants, including harmony figures, customary leaders, educators, Madurese residents, Papuan residents, and supporting informants. The data were analyzed thematically through source and technique triangulation, and were interpreted using the concepts of externalization, objectivation, and internalization in social construction theory. Findings – The results of the study indicate that Madura-Papua relations do not take the form of open communal conflict that occurs continuously, but rather personal and situational tensions triggered by offense, misinterpretation, individual disturbances, socio-economic jealousy, and vigilance toward the security context. At the same time, economic interaction, education, social cooperation, neighborly relations, and communication among figures remain supports for social harmony. The values of tengka and Basudara are internalized through three arenas, namely family, school, and society, which shape the habituation of mutual respect, deliberation, mutual cooperation, politeness, and prudence in cross-group interactions. Originality/Value – This study offers a model of cross-community value internalization that explains how cultural values are habituated, institutionalized, and accepted as social guidelines to reduce conflict vulnerability. This study also contributes to Islamic education studies and religious studies by showing the role of value education, religious moderation, and coexistence in families, schools, and multiethnic communities. Practical Implications – These findings can be used by families, schools, higher education institutions, local governments, FKUB, customary leaders, religious leaders, and harmony organizations to develop multicultural education, interethnic dialogue, local wisdom-based learning, peaceful mediation training, cross-group mutual cooperation activities, and critical literacy. In addition, these findings support the development of value education, religious moderation, social coexistence, and critical literacy in the context of Islamic education and multiethnic society.